Evaluasi Kerja Pembangkit Listrik Tenaga Diesel Gas Dual Fuel PT Indonesia Power Up Bali - Rahmayanti, Wiwi; Bambang Puguh M; Indriyani, Indriyani (SURYA TEKNIKA, 2024)
Gas Diesel Power Plant (PLTDG) is a power plant that can operate with various fuels. In PLTDG PT Indonesia Power UP Bali, there are two modes of operation: diesel mode with single HSD fuel and gas mode with dual fuel (LNG and HSD as pilot fuel). This study evaluates the performance of the Dual Fuel PLTDG at PT Indonesia Power UP Bali. The plant uses a combination of diesel and natural gas. The research methodology involved analyzing operational data during annual performance tests, including fuel consumption, electrical energy generated, engine speed, and fuel heating value. The results show that the use of dual fuel increases the efficiency of the plant compared to the use of a single fuel (diesel). The efficiency of dual fuel use is more linear with respect to load, while that of single fuel use constantly increases with load. The specific fuel consumption in dual fuel use is 16.7% more efficient for the same load than single fuel use. This affects the economic value of generation, where the use of dual fuel with LNG saves 40% compared to the use of single fuel with HSD. In addition, the use of dual fuel with LNG has a positive impact on the environment because it produces more complete combustion. In conclusion, the implementation of a dual fuel system not only improves operational efficiency but also provides environmental benefits by reducing greenhouse gas emissions.